Regulation of Ischemic Neuronal Death by E2F4-p130 Protein Complexes - Iyirhiaro, Grace O.; Zhang, Yi; Estey, Carmen; O'Hare, Michael J.; Safarpour, Farzaneh; Parsanejad, Mohammad; Wang, Suzi; Abdel-Messih, Elizabeth; Callaghan, Steve M.; During, Matthew J.; Slack, Ruth S.; Park, David S. (The Journal of biological chemistry, 2014)
Inappropriate activation of cell cycle proteins, in particular cyclin D/Cdk4, is implicated in neuronal death induced by various pathologic stresses, including DNA damage and ischemia. Key targets of Cdk4 in proliferating cells include members of the E2F transcription factors, which mediate the expression of cell cycle proteins as well as death-inducing genes. However, the presence of multiple E2F family members complicates our understanding of their role in death. We focused on whether E2F4, an E2F member believed to exhibit crucial control over the maintenance of a differentiated state of neurons, may be critical in ischemic neuronal death. We observed that, in contrast to E2F1 and E2F3, which sensitize to death, E2F4 plays a crucial protective role in neuronal death evoked by DNA damage, hypoxia, and global ischemic insult both in vitro and in vivo. E2F4 occupies promoter regions of proapoptotic factors, such as B-Myb, under basal conditions. Following stress exposure, E2F4-p130 complexes are lost rapidly along with the presence of E2F4 at E2F-containing B-Myb promoter sites. In contrast, the presence of E2F1 at B-Myb sites increases with stress. Furthermore, B-Myb and C-Myb expression increases with ischemic insult. Taken together, we propose a model by which E2F4 plays a protective role in neurons from ischemic insult by forming repressive complexes that prevent prodeath factors such as Myb from being expressed. Background: The contribution of E2F4 to hypoxic/ischemic neuronal death is understood poorly. Results: Loss of E2F4 leads to an increase in B-Myb and contributes to hypoxic/ischemic neuronal death. Conclusion: E2F4 is important for survival following hypoxic/ischemic neuronal death. Significance: Targeting E2F4-repressive functions may be important in maintaining neuronal survival under hypoxic/ischemic conditions.